Biocompatibility of Lithium Disilicate and Zirconium Oxide Ceramics with Different Surface Topographies for Dental Implant Abutments - Jung, Susanne (Int J Mol Sci, 2021)
Gingivafibroblasts were cultured on lithium disilicate, on zirconia dioxide, and on titanium with two different surface roughnesses (0.2 µm and 0.07 µm); Proliferation (MTT), Living/Dead staining, cytotoxicity (LDH), proliferation (FGF2), and inflammation (TNFα) were analyzed after 1 day and 21 days. Furthermore, alteration in cell morphology (SEM) was analyzed. The statistical analysis was performed by a Kruskal–Wallis test. The level of significance was set at p < 0.05. There were no distinct differences in cellular behavior between the tested roughness. There were slight differences between tested materials. Cells grown on zirconia dioxide showed higher cytotoxic effects. Cells grown on lithium disilicate showed less expression of TNFα compared to those grown on zirconia dioxide or titanium. These effects persisted only during the first time span. The results indicate that the two tested high-strength ceramics and surface properties are biologically suitable for transmucosal implant components. The findings may help clinicians to choose the most appropriate biomaterial as well as the most appropriate surface treatment to use in accordance with specific clinical dental applications.